Anomaly mediation, Fayet-Iliopoulos D-terms and precision sparticle spectra - Hodgson, R; Jack, I; Jones, D; Ross, G (2005)
We consider the sparticle spectra that arise when anomaly mediation is the source of supersymmetry-breaking and the tachyonic slepton problem is solved by a Fayet-Iliopoulos D-term. We also show how this can lead to a minimal viable extension of anomaly mediation, in which the gauge symmetry associated with this D-term is broken at very high energies, leaving as its footprint in the low energy theory only the required D-terms and seesaw neutrino masses. © 2005 Elsevier B.V. All rights reserved.